Risk Factors for Iron Deficiency Anemia Among Adolescents in Developing Countries: Study Literature Review - Ocktariyana, Ocktariyana; Flora, Rostika; Yuliastuti, Maria Eka; Zulkarnain, Zulkarnain; Lasepha, Ani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescents experience physiological and psychological growth to establish the basis for maturity. The biological well-being of adolescents requires improved nutrition. Intake of foods rich in micronutrients such as iron, zinc, and vitamin A, which are relevant to supporting biological metamorphosis in adolescents, can influence growth and well-being. The aim of this study is to holistically identify the main risk factors affecting adolescents that contribute to anemia in developing country developing.A systematic review was conducted following the guidelines provided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The current review defines adolescents as individuals ranging in age from 10 to 19 years. A total of 2,252 articles were retrieved from the database, of which 618 duplicates were removed and 1,492 records were issued after filtering by title and abstract. 142 articles were fully assessed for notability, and 127 articles were also excluded based on inclusion and exclusion criteria. Finally, 15 studies were included in the systematic review. The review showed that food intake practices, parasite infections, menstruation, the increasing age of adolescent girls, and the low educational status of guardians are the main risk factors for iron deficiency anemia among adolescents in most developing countries.